SINERGI ILMU DAN IMAN: PERAN INTEGRASI AGAMA DALAM PENDIDIKAN MODERN - Marlina, Cut Nyak; Mahmud, Salami; Rahmi, Sri (Institut Agama Islam Sumatera Barat Pariaman, 2025)
Integration of science and religion or faith is important in the modern educational system. Education based on religious integration can help students not only to understand worldly knowledge, but also to have a deep spiritual awareness so that they are able to live a more meaningful and responsible life. The integration of science and faith can be applied to various aspects of education, such as curriculum, learning methods, and the role of educators. This research aims to explore the role of religious integration in modern education. The method used in this research is library research. The results show that the synergy between science and faith or the integration of Islamic teachings in modern education is a strategic step to produce students who are not only intellectually intelligent but also have noble morals and a balanced personality. Islamic education views knowledge as a means to know God and to understand life more fully. Therefore, knowledge and faith must go hand in hand and reinforce each other. Through the process of incorporating Islamic values into every aspect of learning, students not only gain knowledge, but are also guided to become responsible, honest, and highly ethical individuals.